Reconstruction of the Concept of Classical Muamalah Fiqh Contracts as a Foundation for Innovation in the Modern Islamic Financial Industry - Kumaidi Kumaidi; Syukri Iska; Fauzani Fauzani; Fitri Yenti; Jasri Waldi (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
The rapid development of the Islamic financial industry in the digital era demands a conceptual reconstruction of classical Islamic financial contracts to ensure their relevance as a foundation for innovation in modern Islamic financial products. This study aims to analyze the relevance of classical contracts in contemporary Islamic financial products, identify shifts in contract implementation due to digitalization and fintech sharia, evaluate the suitability of the implementation of contracts with the principles of al-sharī'ah, and formulate a conceptual model for adaptive contract innovation that is still based on muamalah jurisprudence. The method used is qualitative with a qualitative approach. Library research, using content analysis techniques, comparative analysis, and normative interpretation based oninyesūl al-fiqh. The results of the study show that classical contracts such asjamḥah, inḍārabah, musyārakah, pilgrimage, wait, regards, and hotyesthehas sufficient normative elasticity to accommodate digital financial innovation, but their implementation still experiences many distortions that are contrary to the substancepoetyesid al-sharī'ahThis research formulates a conceptual model of contract innovation based on four pillars: adaptive normative reinterpretation, integration of Sharia-based technology, reconstruction of equitable risk distribution, and strengthening of Sharia governance. This model offers a framework that can synergistically and sustainably bridge the authority of classical Islamic jurisprudence texts with the pragmatic demands of the modern Islamic financial industry